Childfree and Happy : Transforming the Rhetoric of Women's Reproductive Choices - Wooten, Courtney Adams (Book collections on Project MUSE., 2023)
"Childfree and Happy examines how millennia of reproductive beliefs have positioned women who choose not to have children as deviant. Considering affect and emotion alongside the lived experiences of women who have chosen not to have children, Wooten offers a new lens to feminist scholars' examinations of reproductive rhetorics"--